Water Quality of the Main Water Source of Village Ambassador, Tublay, Benguet using the Allium cepa Test - Doctor, Teresita R.; Manuel, Jay Jay F.; Rivera, Marites P.; Kebasen, Chester A.; Bulayungan, Faize L. (JPAIR Multidisciplinary Research, 2010)
In view of the ecological hazards of chemicals, in vitro experiments were conducted to determine the probable toxicity of the different water samples from the main water source of Village Ambassador, Tublay, Benguet employing the classical Allium cepa test prior to the establishment of communal water catch basins/tanks. In this study, experimental Allium cepa were grown in the different water samples from Lower and Upper Coroz, Baliti, and Salaksak. The different parameters that were utilized in the study (i.e. macroscopic and microscopic) served as indicators of the genotoxicity of the water samples to the test organisms. This laboratory experiment of the genotoxic effect of the water samples revealed insignificant differences among the different water samples and the control group for all the following observations: macroscopic level in terms of root length and frequencies of root forms and the mitotic index values scored at microscopic level. This interaction implies that the different water samples inhibited the growth of the onions, may have caused some morphological abnormalities and possible genotoxic effect on the onions in all the treatment groups. However, the level of toxicity did not vary significantly among the treatment groups and the control group. Taken together, results of the study showed that the selected water samples from the main water source of Village Ambassador may be tapped as possible sources of potable water.
Keywords: water quality; Allium cepa; ecological hazard